AGROBIOLOGICAL FEATURES OF GROWINGSELF-PROPAGATION PLANTING MATERIAL RIBES NIGRUM IN THE NORTHEASTERN FOREST STEPPE OF UKRAINE - Белоконь, Вика; Токмань, Владимир (SWorldJournal, 2021)
The publicationreflects the results of the study on the self-propagation of Ribesnigrum "Kopan’ Jubilee" from woodycuttingsintoone, two and threebuds. The influence of metamerism of cuttings on the level of growthprocesses in Ribesnigrumplantswasrevealed